2017
DOI: 10.1016/j.jand.2016.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Comprehensive Assessment of Food Parenting Practices: The Home Self-Administered Tool for Environmental Assessment of Activity and Diet Family Food Practices Survey

Abstract: Background Parents' food parenting practices have a significant influence on children's dietary intake and risk for obesity and chronic disease. Understanding the impact and interactions between parents' practices and children's behavior is limited by a lack of development and psychometric testing and/or limited scope of current measures. HomeSTEAD (Home Self-administered Tool for Environmental assessment of Activity and Diet) was created to address this gap. Objective This paper describes development and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…found that active guidance of food consumption was related to the higher consumption of healthy foods, mediated through attitude towards consuming healthy foods. Likewise, Vaughn et al (2017) found that nutrition education was related to higher consumption of fruits and vegetables, and lower consumption of sweets. Despite its potential importance, there have been little conceptual development of the construct, leading to conceptual ambiguity between active guidance, nutrition education, reasoning, and encouragement, resulting in potentially problematic operationalization (Lwin et al, 2017;Vaughn et al, 2016 This aim of this study is to explicate the concepts of active and restrictive guidance of food consumption, and to operationalize the constructs using a variety of item-generation and scale validation techniques, so that it can offer some clarity into their effects on child food consumption.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…found that active guidance of food consumption was related to the higher consumption of healthy foods, mediated through attitude towards consuming healthy foods. Likewise, Vaughn et al (2017) found that nutrition education was related to higher consumption of fruits and vegetables, and lower consumption of sweets. Despite its potential importance, there have been little conceptual development of the construct, leading to conceptual ambiguity between active guidance, nutrition education, reasoning, and encouragement, resulting in potentially problematic operationalization (Lwin et al, 2017;Vaughn et al, 2016 This aim of this study is to explicate the concepts of active and restrictive guidance of food consumption, and to operationalize the constructs using a variety of item-generation and scale validation techniques, so that it can offer some clarity into their effects on child food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, parents are educators, role models, and gatekeepers in the lives of their children (Case & Paxson, 2002). In the context of food consumption, public health and health communication researchers have identified several food-related parenting practices which are key determinants of child food consumption (Vaughn et al, 2016;Vaughn, Dearth-Wesley, Tabak, Bryant, & Ward, 2017;Vaughn, Tabak, Bryant, & Ward, 2013a;Yee, Lwin, & Ho, 2017). In order to better understand how parents can promote healthy behaviors among children, it is important to situate the question within a meaningful theoretical framework that seeks to explain the influence of social contexts on children and vice versa.…”
Section: Socialization Theorymentioning
confidence: 99%
See 3 more Smart Citations